Relationship between Nutrition Deficiency, Oral Cavity Hygiene, and Oral Candidiasis in a 10-Years-Old Child - Sri Hernawati (Health Notions, 2019)
Candida albicans (C.albicans) is the main causative agent in oral candidiasis. Candida spp is a commensal microorganism or normal flora in the mouth without causing symptoms. Candida spp can be a pathogen when the body's condition decreases, systemic medical therapy for a long time, nutritional deficiencies and poor oral hygiene. This study aimed to determine the predisposing factors for the causes of oral candidiasis in 10-year-old pediatric patients who came to the Department of Oral Medicine, Dental Hospital of Dentistry Faculty of Jember University. The results of this study indicate a relationship between nutritional deficiencies and poor oral hygiene with oral candidiasis in children. White pseudomembranous plaque lesions are mostly found in the dorsal area of the tongue. Therapy for the patients is by applying nystatin anti-fungal, multivitamins, and education to improve nutrition and oral hygiene. Keywords: nutritional deficiency; the oral cavity hygiene; oral candidiasis